Neutral [2]rotaxane host systems that recognise halide anions in aqueous solvent mixtures. - Mercurio, J; Tyrrell, F; Cookson, J; Beer, P (2013)
Four pyridine N-oxide axle containing [2]rotaxanes have been synthesised via an anion templated threading-followed-by-stoppering strategy and shown to be the first examples of neutral interlocked host systems capable of recognising halide anions in aqueous solvent mixtures.